Pemodelan ramalan trend penyakit Influenza H1N1 menggunakan model bersepadu Seiqre - Emmerline Shelda Siaw,; Saratha Sathasivam,; Sabastine, Emmanuel; Adebayo, Salaudeen Abdulwaheed (Penerbit Universiti Kebangsaan Malaysia, 2025)
The H1N1 influenza outbreak, which initially infected over 15,000 individuals in Malaysia, served as a stark warning to healthcare professionals and all stakeholders in Malaysia and global health sectors. This study proposes SEIQRE model to manage and prevent the spread of influenza through quarantine strategies and natural recovery mechanisms. By employing the Runge-Kutta method, the study provides deeper insights into the dynamics of H1N1 influenza and develops effective strategies to mitigate transmission and reduce risk in high-prevalence areas. Analysis of key epidemiological parameters reveals that reinfection plays a significant role in triggering a backward bifurcation, challenging the conventional reliance on a basic reproduction number less than one. A modified model excluding reinfection confirms a forward bifurcation. These findings underscore the importance of incorporating quarantine, bifurcation effects, and scaling factors into effective infection control strategies. This research contributes to global efforts to combat the H1N1 pandemic and safeguard public health in Malaysia.